2019
DOI: 10.1016/j.actbio.2019.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear elasticity of the lung extracellular microenvironment is regulated by macroscale tissue strain

Abstract: The extracellular matrix (ECM) of the lung provides physical support and key mechanical signals to pulmonary cells. Although lung ECM is continuously subjected to different stretch levels, detailed mechanics of the ECM at the scale of the cell is poorly understood. Here, we developed a new polydimethylsiloxane (PDMS) chip to probe nonlinear mechanics of tissue samples with atomic force microscopy (AFM). Using this chip, we performed AFM measurements in decellularized rat lung slices at controlled stretch level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 59 publications
10
45
0
Order By: Relevance
“…After 24 h of treatment, the increase of specific lung elastance suggested a stiffening of the ventilatable lung, possibly due to the increased rate of stress and strain application and/or impaired surfactant functioning. 19,20 High PEEP Groups. The application of high PEEP with two levels of mechanical power induced tremendous stress and strain.…”
Section: Discussionmentioning
confidence: 99%
“…After 24 h of treatment, the increase of specific lung elastance suggested a stiffening of the ventilatable lung, possibly due to the increased rate of stress and strain application and/or impaired surfactant functioning. 19,20 High PEEP Groups. The application of high PEEP with two levels of mechanical power induced tremendous stress and strain.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Polio et al (2018), measured Y ae in porcine lung using cavitation rheology (6.1 ± 1.6 kPa), small amplitude oscillatory shear rheometry (3.3 ± 0.5), microindentation (1.4 ± 0.4), and uniaxial tension (3.4 ± 0.4) and showed that all these techniques provided values in the same range. Using AFM, Liu and Tschumperlin (2011) estimated a value around 5 kPa for mice, while Jorba et al (2019) obtained values around 10 kPa at low strain in rats. Cavalcante et al (2005) used their network model to estimate the effective alveolar wall stiffness to be ∼5 kPa.…”
Section: Discussionmentioning
confidence: 99%
“…Another important simplifying assumption in the analytical model is that the stress-strain behavior of the alveolar wall is linear with a constant elastic modulus. A recent study used atomic force microscopy (AFM) to measure alveolar septal wall stiffness in decellularized rat lung tissue and found that indentation stiffness increased from about 10 kPa at 0 strain to about 80 kPa at 0.3 strain (Jorba et al, 2019). While the mechanism underlying this non-linear behavior remains unclear, one possibility is that it reflects the progressive straightening of flaccid fibers (Sobin et al, 1988;Mercer and Crapo, 1990;Toshima et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…As the venous return increases, the heart increases its force of contraction and resulting stroke volume. In contrast, the lungs possess a nonlinear elasticity owing to their extracellular microenvironment 46,47 . As the diaphragm contracts, a negative intrapleural pressure expands the lungs.…”
Section: Discussionmentioning
confidence: 99%